Transnational migration and human security the migration-development-security nexus - Truong, Thanh-Dam; Gasper, Des (Hexagon series on human and environmental security and peace, 2011)
This volume addresses key aspects of human security in transnational migration. The 22 essays cover all levels of migration systems, from families, farms and firms through to global organizations and negotiating forums. They show how institutional frameworks for cross-border movements of people, finance, and goods have co-evolved with changes in the workings of nation-states. They thereby reveal aspects of power and privilege within international migration as a discursive area and at its intersections with the fields of development, governance and security. Revisiting presuppositions that have been taken as givens, and exploring their role in shaping rules and institutions that control the movements of people across and within borders, the essays reveal also the mentalities and rationalities that have made up and continue to make up the reality of transnational migration today. A human security perspective can encourage exploratory thinking and provide conceptual space for deeper understandings of human, movement and borders, to help overcome the limits of conventional analytical and policy dualisms and dichotomies.